School discipline: a conceptual approach for a research project with students, parents and teachers (2020)
Some conceptual approaches in educational psychology regarding the study of school disciplinary practices are reviewed, emphasizing the importance of recovering the voices of the school's actors - teachers, students and acudientes- and their intersubjective relationships. Additionally, it includes the study of the actor's expectations about students' formation in the school, as a category implicit in the actors' perceptions regarding school discipline, and has not been the subject of interest in the studies reviewed. Finally, three objectives are proposed: (1) identify the perceptions of students, parents and teachers regarding the school disciplinary practices; (2) identify their expectations for students' formation at school; and (3) contrast their perceptions regarding school discipline and students' formation